A linguagem musical nas práticas alfabetizadoras da Educação do Campo - Souza, Aline dos Santos (Brasil, 2023)
This research with a qualitative approach aims to analyze the contribution of musical language in literacy practices in a rural school in the municipality of Barreirinha-AM. The field research was carried out in a public school located in the Terra Preta do Limão District, in the municipality of Barreirinha - AM, and data collection took place in two classes in the early years of Elementary School (literacy cycle) through participant observation and conversation wheel with educators. The results of the study reveal that music is a textual genre of the artistic-literary field, which has the most diverse meanings in cultural manifestations, that is why this language in the literacy/literacy processes of the rural school is essential, because it gives the literacy students an interest , concentration, perception, communication, memory activation, as the sound, rhythm, melody, harmony and lyrics of songs are important aspects for the cognitive, motor and linguistic development of students, it also contributes to valuing and articulating knowledge locations, socio-cultural experiences and social interaction of children in the countryside.